Implementing data science to enhance water distribution system modelling. A case study of building hydraulic model of high-pressure zone in Wrocław - Dykiert, Karol; Cieżak, Wojciech; Bródka, Piotr (Instal, 2025)
This study presents the development and calibration of a hydraulic model for a high-pressure zone (HPZ) within the water distribution network (WDN) of Wrocław. The work focuses on advanced data processing methods and calibration techniques to improve model accuracy, drawing upon established concepts from both environmental engineering and data science. Our results indicate a very good model fit, although with minor inconsistencies regarding pipe roughness calibration. The overall approach demonstrates how the integration of statistical, hydraulic, and optimisation techniques can lead to robust and reliable WDN modelling, supporting both academic and operational needs.
Keywords: water distribution system modelling; data science; water distribution network; evolutionary algorithm; heuristic approach; artificial intelligence